1999
DOI: 10.1111/j.1600-0536.1999.tb05968.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoses in cement workers in southern Taiwan

Abstract: Construction workers are known to have occupational dermatoses. The prevalence of such dermatoses was unknown in Taiwanese construction workers. The objective of this study was to determine the work exposure, prevalence of skin manifestations, and sensitivity to common contact allergens in cement workers of southern Taiwan. A total of 1147 current regular cement workers were telephone-interviewed about skin problems during the past 12 months, work exposure, and personal protection. Among those interviewed, 166… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 19 publications
1
18
1
2
Order By: Relevance
“…The mean duration of being a cement worker was around 27 years, which is approximately 10 years longer than reported previously by Guo et al 5 The location of affected skin was predominantly the hand, which was strongly consistent with previous observations. 5 The most common skin manifestation among cement workers was thickening of the skin over the dorsal surface of the hand (64.9%), as well as hyperkeratosis over the palm (59.8%) ( Table 2). Further significant manifestations included scaling (35.1%), erythema (25.8%), dryness (33%), fissure (20.6%) and hyperpigmentation (14.4%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The mean duration of being a cement worker was around 27 years, which is approximately 10 years longer than reported previously by Guo et al 5 The location of affected skin was predominantly the hand, which was strongly consistent with previous observations. 5 The most common skin manifestation among cement workers was thickening of the skin over the dorsal surface of the hand (64.9%), as well as hyperkeratosis over the palm (59.8%) ( Table 2). Further significant manifestations included scaling (35.1%), erythema (25.8%), dryness (33%), fissure (20.6%) and hyperpigmentation (14.4%).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies in Europe and the USA have shown that the prevalence rate of chromium hypersensitivity among cement workers is around 4e5%. 6,7 However, some countries show a very high prevalence rate, for example Taiwan 13%, 5 Poland 23% 8 and Singapore 40%. 9 In this study, the positive rate of chromium hypersensitivity among the cement workers was as high as 24.5% (Table 3).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Önceki çalışmalarda çalışmamızla benzer olarak inşaat işçilerinde çimentonun içeriğinde bulunan potasyum dikromat hipersensitivitesi yüksek raporlanmıştır 8,[25][26][27] . Yapılan çalışmalar çimentoya ferik sülfat katılmasının potasyum dikromat duyarlılığını azaltmada etkili olduğu gösterilmiştir 28 .…”
Section: Grafikunclassified
“…Normally, the conference is organized by an academic association or a university, and is sponsored by governmental agencies like CLA, DOH, and MOE. Quite a few researches in locating the underlining causes of occupational disease or outbreak have been successfully performed by independent researchers or scholars from universities and colleges and appreciable results have been continuously obtained [5][6][7][8][9][10][11][12][13][14][15][16][17][18] . The participation of governmental agency, however, might be more resourceful in setting up a nationwide surveillance program or develop a control remedy or for further corresponding policy-making 19,20) .…”
Section: Research Activitiesmentioning
confidence: 99%